The Effectiveness of the Circ Model with the Help of Flashcard Media on the Learning Outcomes of Science Class V - Saputri, Ayunda Nadea; Kaltsum, Honest Ummi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study evaluates the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model supported by flashcard media in improving science learning outcomes for class VA students at MI Muhammadiyah Gonilan. Methodology: Using A Pre-Experimental One Group Pre-Test and Post-Test Design, The Sample Included 29 Students. Data Collection Involved Tests (Pre-Test and Post-Test) and Interviews With The Class Teacher. The Data Were Analyzed Using Normality, Homogeneity, Paired Sample T-Test, and N-Gain Tests. Results: Results Indicate Moderate Effectiveness, With A T-Test Value Of 19.239 > 2.048 Showing Significant Differences Between Pre-Test and Post-Test Scores. The N-Gain Score Of 68.65% Falls In The Medium Category. Applications/Originality/Value: The Findings Suggest That the CIRC Model With Flashcard Media Moderately Improves Learning Outcomes and Highlights The Potential For Innovative, Easily Implemented Teaching Strategies To Enhance Classroom Learning.